Twisted, Urban and Visionary Landscapes in Contemporary Painting. - Bloemheuvel, Marente; Buck, Louisa; Damianovic, Maia; Debbaut, Jan; Drohojowska Philip, Hunter; Friis-Hansen, Dana; Godfrey, Mark; Green, Alison; Guldemond, Jaap; Hettig, Frank-Alexander; Pryde, Josephine; Volk, Gregory; et al. (Rotterdam : NAI Uitgevers Rotterdam, 2000)
Twisted, Urban and Visionary Landscapes in Contemporary Painting includes the work of twelve international painters. A defining characteristic of these artists is their figurative, visual language. This is not so much a reference to a tangible reality, but rather to a reality that is artificial, otherworldly or fabricated. Some of the artists are interested in a reality mediated by video and computer games, television, film, advertising and other media expressions. Other artists use different references to achieve an artificial reality. In both cases it is a reality that is completely man-made, manipulated and synthetic ; for removed from Normal reality. Many of the works are characterised by artificial use of colour, sampling of disparate elements, and patterns thar are almost abstract. This creates a world that,, on the one hand, tends to exalt its very impermanence and, on the other hand, has a disconcerting undertone. Each chapter spotlights one artist, offers an extensive array of visual material and furnishes on accompanying explicative text.An essay by Jaap Guldemond and Marente Bloemheuvel (curators at the Stedelijk Van Abbemuseum) provides a context for and an explanation of the principles and premisses of this theme.
Armstrong, L.C. ; Broek, Hans ; Dalwood, Dexter ; Doig, Peter ; Ellis, Sharon ; Finley, Chris ; Morris, Sarah ; Morrison, Paul ; Murakami, Takashi ; Raedecker, Michael ; Thorpe, David ; Tomaselli, Fred
biog., ind. tent., gr. tent., bibliog. p. 71-79
Engels
Twisted, Urban and Visionary Landscapes in Contemporary Painting, Van Abbemuseum Eindhoven, September 23 - November 26, 2000
boek